PERIOPERATIVE ANAPHYLAXIS: A SYSTEMATIC REVIEW - Ma’bud, Tasia (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Background: Perioperative anaphylaxis can be associated with antibiotics, neuromuscular blocking agents, dyes, latex, and disinfectants. This article evaluates the condition's epidemiology, pathophysiology, and treatment, including an allergy assessment. Aim: This investigation aims to investigate the possibility that perioperative anaphylaxis develops. Methods: The study met the PRISMA 2020 guidelines through self-evaluation. The investigators ensured the study's current became feasible. Publications from 2015 to 2023 were searched using various online reference databases, including Pubmed and SagePub. Excluded were review papers, pre-existing publications, and incomplete articles. Result: The search generated 552 and 321 articles in the PubMed and SagePub databases, respectively. 54 articles were found for PubMed and 21 for SagePub in the investigation conducted for the last year of 2015. A total of 18 papers were collected, with 12 generated from PubMed and 6 from SagePub. We included five studies that met the criteria. Conclusion: The presence of anesthetics, surgical settings, and various medications and substances may complicate the process of accurate diagnosis. A systematic approach was used to identify the reaction, perpetrator, and future management. Effective management of perioperative anaphylaxis requires close coordination among anesthesiology, surgery, and allergy specialists.